2017
DOI: 10.1017/s095457941700133x
|View full text |Cite
|
Sign up to set email alerts
|

A neurocomputational investigation of reinforcement-based decision making as a candidate latent vulnerability mechanism in maltreated children

Abstract: Alterations in reinforcement-based decision making may be associated with increased psychiatric vulnerability in children who have experienced maltreatment. A probabilistic passive avoidance task and a model-based functional magnetic resonance imaging analytic approach were implemented to assess the neurocomputational components underlying decision making: (a) reinforcement expectancies (the representation of the outcomes associated with a stimulus) and (b) prediction error signaling (the ability to detect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 96 publications
(181 reference statements)
3
61
0
1
Order By: Relevance
“…Neural activation in a group of children and adolescents exposed to independently documented maltreatment experience ( N = 18) was contrasted with that in a group of carefully matched peers ( N = 19). Maltreatment experience was found to be associated with a pattern of reduced activation to reward cues in the striatum, and in other regions implicated in outcome representation, including the orbitofrontal cortex and insula (Gerin et al., in press).…”
Section: Functional Magnetic Resonance Imaging and The Study Of Childmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural activation in a group of children and adolescents exposed to independently documented maltreatment experience ( N = 18) was contrasted with that in a group of carefully matched peers ( N = 19). Maltreatment experience was found to be associated with a pattern of reduced activation to reward cues in the striatum, and in other regions implicated in outcome representation, including the orbitofrontal cortex and insula (Gerin et al., in press).…”
Section: Functional Magnetic Resonance Imaging and The Study Of Childmentioning
confidence: 99%
“…To date, functional neuroimaging studies of adolescents indicate that childhood maltreatment leads to alterations in reward processing systems in subcortical reward‐related areas, such as the striatum. Teicher and Samson () have proposed that heightened threat reactivity alongside blunted anticipatory responses to reward (Hanson et al., ; Gerin et al., in press), may reflect an adaptive calibration towards an avoidant response during approach‐avoidance conflict situations, increasing likelihood of survival in an environment characterized by danger. However, they note that such altered responsiveness may confer increased risk of depression/anhedonia (Pizzagalli et al., ; Wacker, Dillon, & Pizzagalli, ), anxiety (Etkin et al., ; Redlich et al., ) and addiction (Balodis & Potenza, ; Corral‐Frías et al., ).…”
Section: Functional Magnetic Resonance Imaging and The Study Of Childmentioning
confidence: 99%
“…When mental health problems do arise, they tend to be associated with an earlier onset of symptoms, greater comorbidity, and poorer responsiveness to traditional interventions (Agnew-Blais et al, 2016;Nanni et al, 2012). Over the last decade, neuroimaging studies have begun to document alterations in neuro-cognitive functioning associated with maltreatment exposure across a number of domains (Gerin et al, 2017). The theory of latent vulnerability postulates that these alterations can be understood in part as adaptations to early adverse or neglectful environments in line with the notion of experiential canalization; the idea that abilities are shaped by the interaction of our biology and experience (Blair & Raver, 2012;McCrory & Viding, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood maltreatment is associated with neurodevelopmental disruption, 1 psychopathology 2,3,4,5 (ie, heightened threat sensitivity 6,7,8,9 ), heightened amygdala responsiveness, 10,11,12 and disrupted reinforcement-based decision making. 13,14,15 Maltreatment may also be associated with executive dysfunction, although there is some inconsistency in the findings. 16,17,18,19 Two studies examining response control reported increased responsiveness within the dorsal cingulate cortex and midcingulate cortex and precentral and postcentral gyri during response control in maltreated children and adolescents.…”
Section: Introductionmentioning
confidence: 99%